1998
DOI: 10.1007/bf02458373
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between growth in gross domestic product (GDP) and growth in the chemical engineering literature in five different countries

Abstract: Data were compiled and linearly correlated on the growth in the gross domestic product (GDP) with the academic chemical engineering literature over a recent 26-year period for five different English-speaking countries, namely, the United States, Canada, Great Britain, India and Australia. The publication figures were also scaled to the total number of chemical engineering schools in the country; furthermore, all of these data were normalized from zero to unity, using the figures for the most recent year (1996)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…A number of previous literature has used citation analysis for the evaluation of research output quality to establish a link between research output and economic growth (Price 1978;Kealey 1996;Hart and Sommerfeld 1998;Haiqi and Yuha 1997;Pouris 2003). Nevertheless, research publication is a more accurate measure of research achievement and innovation of a country (Pouris and Pouris 2008;Inglesi-Lotz and Pouris 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of previous literature has used citation analysis for the evaluation of research output quality to establish a link between research output and economic growth (Price 1978;Kealey 1996;Hart and Sommerfeld 1998;Haiqi and Yuha 1997;Pouris 2003). Nevertheless, research publication is a more accurate measure of research achievement and innovation of a country (Pouris and Pouris 2008;Inglesi-Lotz and Pouris 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Hart and Sommerfeld (1998) examined the relationship between economic growth and the growth in chemical engineering literature -but not the total literature. As is argued in their paper, "the field of chemical engineering, perhaps because of its small but well defined area of technical endeavour, is often used in the performance of scientometric and science policy studies" (Hart & Sommerfeld, 1998:300 Their analysis concluded, among others, that there were "...positive pay-offs in terms of output growth, investment performance as well as efficiency gains" (Fedderke & Schimer, 2006:149).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The gap between the countries of the two regions on the one hand, and between Romania and the other Eastern European countries on the other hand can be explained by their different levels of economic development. Hart and Sommerfeld (1998) have shown that the total number of publications in a country is closely related to the country's gross domestic product. In other words, it is obvious that scientific development can not be dissociated from the level of economic development of a country.…”
Section: Research Resultsmentioning
confidence: 99%